Berczeli Anzelm Károlyhoz - Fejes Mari (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1959)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek